The Paradoxical Power of Continuous Assessment Learning Activity Nexus Industrial Development in the Context of Zimbabwean Education System 5.0 - Firomumwe, Thomas (Journal of Economics Education and Entrepreneurship, 2022)
The present study aimed at exploring the power of Continuous Assessment Learning Activity in connection with industrial development in Zimbabwean education system version 5.0. The education system in Zimbabwe has undergone a transformation in a proposition to industrialise the economy through education as nodded in National Development Strategy for vision 2030 middle income class economy. Thus, the objective of this research was hinged on establishing the industrial skills imposed in learners by CALA a version of curriculum innovation. The study also set an objective of finding evidence of industrial development from CALA and establishing teacher’s attitude towards implementation of CALA. The study adopted phenomenological qualitative research study in which systematic sampling was used to select 14 respondents for interviewing over WhatsApp. The study revealed that CALA impose and sharpen research, practical, problems solving and creative skills in learners. As well learners are involved in producing products for sale and developed their entrepreneurship skills. Teacher’s attitude showed a negative attitude towards implementation of CALA in schools due to lack of support, poor remuneration and lack of training. The research recommends measure to boost teacher’s attitude towards CALA for industrial development.